Zooarchaeological Collection from Bolshepichuginsky Kurgan Burial Mound (According to the Excavations in 2013–2016)* - S. S. Onischenko; P. V. German; M. M. Devyashin; A. N. Sidelnikova (Вестник Кемеровского государственного университета, 2019)
Numerous animal remains are part of burial practice in Tagar culture, therefore researches conducted to determine anatomic, specific, and age structure of zooarchaeological assemblages in certain tombs and whole cemeteries, their peculiarities and comparative analysis. The paper features an analysis of the faunistic collections from the kurgan burial mound of Tagar culture Bolshepichugino I (VI century – C.E.). In total, 75 samples from kurgan 13 were described and 2192 – from kurgan 16 have. The zooarchaeological assemblages consist of remains of a horse, cattle, and sheep, fox, doe, Asian badger, mountain hare, and birds. The peculiarities of the associated food were determined (scapula, 3–4 ribs, femur, and tibia of cattle and sheep). The use of right parts of animal bodies is discussed in the context of burial practice in the Early Tagar period. Remains of young animals (younger than 1 year) were also found in the  materials. It is supposed that the burial mounds were made in winter time. Some domestic and wild bone assemblages located in different places of the kurgans are considered to belong to another period and culture or zoogenic processes. A special attention is paid to the doe and fox remains in the tombs since their carcasses might have been used in burial rituals. In total, the composition and specifics of zooarchaeological materials make it possible to speak about similarity of forest-steppe and steppe early Tagar assemblages in this aspect of burial practice.